Physical characterisation of an alginate/lysozyme nano-laminate coating and its evaluation on ‘coalho’ cheese shelf life - Medeiros, B. G. S. (2014)
This work aimed at the characterisation of a nanolaminate coating produced by the layer-by-layer methodology and its evaluation on the preservation of ‘Coalho’ cheese. Initially, five alternate layers of alginate and lysozyme were assembled in an aminolysed/charged polyethylene terephthalate (A/C PET) and physically characterised by UV/VIS spectroscopy, contact angle, water vapour (WVTR) and oxygen (OTR) transmission rates and scanning electron microscopy. Afterwards, the same methodology was used to apply the nano-laminate coating in ‘Coalho’ cheese and its shelf life was evaluated during 20 days in terms of mass loss, pH, lipid peroxidation, titratable acidity and microbial count. UV/VIS spectroscopy and contact angle analyses confirmed the layers’ deposition and the successful assembly of nano-laminate coating on A/C PET surface. The coating presented WVTR and OTR values of 1.03×10−3 and 1.28× 10−4 g m−2 s−1, respectively. After 20 days, coated cheese showed lower values of mass loss, pH, lipidic peroxidation, microorganisms’ proliferation and higher titratable acidity in comparison with uncoated cheese. These results suggest that gas barrier and antibacterial properties of alginate/lysozyme nanocoating can be used to extend the shelf life of ‘Coalho’ cheese.